Integration of Islamic Teachings in Character Education to Strengthen Morality and Ethics in Schools - Romzi, Moh; Noviyanti, Shobihatul Fitroh; Hamidah, Tutik; Fawaid, Ahmad (Universitas Al-Amien Prenduan, 2024)
This study aims to examine the implementation of Islamic-based character education to build morality and ethics in educational institutions by integrating Islamic values into curricula, teaching methods, and extracurricular activities. Using the library research method, data were collected from journals, books, policy documents, and scholarly articles. In-depth analysis identified key concepts, principles, and best practices in Islamic-based character education. The findings reveal that a holistic approach involving teachers, students, parents, and communities is essential for success. Islamic-based character education effectively fosters individuals with strong morality, character resilience, and ethical commitment. The study provides practical recommendations for educators and policymakers to design relevant and effective character education programs that address modern moral challenges.